Pengaruh Penggunaan Tepung Gaplek dan Tempe Masing-masing Sebagai Sumber Energi dan Protein pada Anak Ayam - Ibnu Katsir; Nasition N S; Kadarwati Kadarwati (Buletin Ilmu Makanan Ternak, 1986)
Six groups of male chicckens were fed with three experimnental diets consisting mainly of Yellow corn-Fish meal-Soybean oil meal (YFS), Cassava-tempe meal (CT), and Cassava-tempeh-sifh meal (CTF). Main objectives of the study were : 1).To evaluate wether the CT ration could meet the energy and the protein requirements, 2). To Study the nitritive velnes of tempeh (Fermented Soybean), and 3). To compare the effects of the experimental diets on body composition. It was apparent from the experiment that the chickens on the CT diet performed poorer in terms of gain, feed consumption, feed conversion, and Nitrogen retention as well as protein deposition in the whole carcass. Animal performance was improved when the tempeh was partially substituted with fish meal (CTF diet). It seems that a diet of plant protein only was inferior to animal protein supplemented diets.